Hurricane Sandy: inside the megastorm [videorecording (DVD)] - Tibbon, Talya; Johnson, Corey (PBS Distribution, 2013)
Inside the Megastorm takes viewers moment by moment through Hurricane Sandy, its impacts and the future of storm protection. Through first person accounts from those who survived, and from experts and scientists, Inside the Megastorm gives scientific context to a new breed of storms.